Chemical profiling and biological properties of Neolitsea kedahense Gamble essential oils. Issue 23 (2nd December 2017) - Jani, Nor Akmalazura; Sirat, Hasnah Mohd; Ahmad, Farediah; Mohamad Ali, Nor Azah; Jamil, Mailina
Abstract: Hydrodistillation of the fresh stem and leaf of Neolitsea kedahense Gamble, collected from Gunung Jerai, Malaysia followed by the GC-FID and GC-MS analysis revealed the detection of a total of 47 constituents of which 28 (86.4%) from the stem and 31 (96.4%) constituents from the leaf. δ -Cadinene (17.4%), 1- epi -cubenol (11.8%), cyperotundone (9.0%), cis -cadin-4-en-7-ol (7.7%), τ -cadinol (7.1%) and α-cadinol (7.1%) were the principle constituents in the stem oil, whereas β -caryophyllene (18.9%), bicyclogermacrene (18.6%) and trans -muurola-4(14), 5-diene (9.8%) were the major constituents in the leaf oil. Among the identified constituents, three constituents namely 7- epi -α-selinene, junenol and cis -cadin-4-en-7-ol have not been found previously from Neolitsea oils. The stem and leaf oils were screened for their α-glucosidase inhibitory and antibacterial activities. Both oils displayed potential α-glucosidase inhibitory activity, while the stem oil possessed weak antibacterial activity against Bacillus subtilis . Abstract :